ACCOUNTING AND FINANCIAL REPORTS IN THE FUNCTION OF CORPORATE GOVERNANCE - Aničić, Jugoslav; Aničić, Dušan; Majstorović, Aleksandar (Journal of process management and new technologies, 2017)
Market economy development is highly dependent upon accounting data reliability and financial report quality because the investors decide more easily on investments in the market which had earned trust and safety in the previous period. Big financial scandals from the beginning of the 21st century and still actual financial crisis at the global level have especially contributed to that. The information prepared on the basis of high quality, transparent and comparable international standards considerably reduce investment risks as well as the cost of raising capital. On the other hand, the management of a large number of companies is focused on the creation of short-term personal benefits as opposed to the investors primarily interested in company survival and growth, that is, long-term goals. Information asymmetry is often present in the financial markets, and its damaging results, as a rule, are borne by shareholders and other stakeholders of the company. Corporate governance depends on legal, regulative and institutional environment, and it should balance the interests of the shareholders, capital owners, managers as well as company business managers.